Aroma compounds in eleven edible mushroom species: relationship between volatile profile and sensorial characteristics - Pinho, P. Guedes de (2011)
Wild edible mushrooms, are consumed a lot in many countries, being cooked or eaten in salads. Their culinary and commercial value is mainly due to their organoleptic properties, namely aroma and flavour. In addition, the aroma is very characteristic for each mushroom species, which determines the distinction between them (1, 2). Despite the high consumption of mushrooms, little work is available concerning· their volatile composition. Tras-os-Montes region (north-east.em Portugal) is known for the variety of its soils and diversity of climate conditions.